APLIKASI SURVEI KEPUASAN MASYARAKAT (SKM) BERBASIS ANDROID DALAM MENINGKATKAN PELAYANAN DISDUKCAPIL PURWOREJO - Rasyid, Muhammad Yusfa (Jurnal Ekonomi dan Teknik Informatika (JNETI), 2025)
This Android-based Community Satisfaction Survey (CSS) application aims to measure community satisfaction as service users and improve the quality of public service delivery at the Purworejo Population and Civil Registration Office. The survey currently used is still a questionnaire with closed and open answers, so if a questionnaire is found that is damaged and not filled out completely, then the questionnaire is not included in the data analysis. This application requires observation at the Purworejo Dukcapil Office to obtain the required data. The analytical method used is the sample method taken using simple random sampling and descriptive quantitative techniques where the data is in the form of numbers and analyzed using descriptive statistical analysis techniques for data collection and system development. Meanwhile, the data collection method uses observation, interviews and literature study methods, and the application development method uses the Java programming language and SQLite database. The results obtained from this research are in the form of an Android-based survey application, making the data processed more accurate.